Patient-Reported Symptoms Compared With Nephrologist Documentation During Outpatient Visits: A Retrospective Patient-Reported Outcome Measures Study - Kendra E. Wulczyn; Annie Liu; James P. Lash; Mallika L. Mendu; Sahir Kalim (Kidney Medicine)
Rationale & Objective: Communication of symptom presence between patients and nephrologists is a key step toward management of the symptom burden faced by many patients with chronic kidney disease (CKD), but whether symptoms are being routinely discussed during ambulatory non-dialysis nephrology encounters is uncertain. This study compared patient reports of 11 CKD-related symptoms with nephrologists’ documentation of symptom presence in the concomitant visit note. Study Design: A retrospective analysis of patient-reported outcome measures and nephrologist documentation in the electronic health record (EHR). Setting & Study Populations: Adults treated at 2 ambulatory nephrology practices within a single tertiary academic center in the United States from 2015 to 2020. Data Extraction: Patients reported symptoms using the Kidney Disease Quality of Life Short Form (KDQOL-SF) instrument before clinic visits. Symptoms were identified in the EHR-based note by natural language processing with subsequent manual identification of the context. Analytical Approach: Sensitivity and specificity of nephrologist documentation for symptoms were calculated using KDQOL responses as the reference standard and stratified by numerous patient, nephrologist, and encounter characteristics. Results: Over 4 years, 1,534 patients completed 2,118 KDQOL surveys before visits with 45 nephrologists. Average sensitivity of nephrologist documentation for symptoms was 16% (and <40% for each individual symptom), with an average specificity of 98%. Sensitivity of documentation for symptoms was higher when the patient was female, had an estimated glomerular filtration rate of <30 mL/min/1.73 m2, or had a history of cardiovascular disease. The documentation sensitivity of nephrologists was higher if they were female or were in practice for ≤7 years as compared with >25 years. Limitations: Nephrologist documentation in the EHR may not accurately represent what was discussed during a visit. Conclusions: Accuracy of nephrologist documentation for the presence of CKD-related symptoms in the EHR is low. Although recognizing that symptoms may have been assessed but not documented, the low proportion of clinic notes correctly identifying patient symptoms in this study suggests an opportunity for tools to streamline and standardize symptom assessment in this patient population. Plain Language Summary: This study aimed to characterize how accurate the documentation of nephrologists is when it comes to patient-reported symptoms commonly associated with chronic kidney disease. Patients completed an electronic questionnaire regarding their symptoms before visits at 2 general nephrology clinics, and the responses were compared with documentation in the electronic health record by their nephrologists. We found that despite a prevalence higher than 50% for some symptoms related to chronic kidney disease, the proportion of nephrologist notes correctly identifying symptom presence averaged 16%. We believe this suggests a likely gap in communication between patients and nephrologists regarding symptoms and believe that tools for standardizing symptom assessment in routine nephrology care may help bridge this gap.